IPBES : a story of despair, hope, and bravery :Powerpoint - Willemen, L. (University of Twente, 2020)
Biodiversity and ecosystem services declining at unprecedented rate; Governments agreed in 2010 a need to establish an independent intergovernmental body; The science-policy niche of IPBES; The 4 functions of IPBES; How is IPBES organised?; 4 Objectives and 18 Deliverables.